Adolescent and Parent Experience of Care at a Family-Based Treatment Service for Eating Disorders - Hughes, Elizabeth K.; Poker, Suzannah; Bortz, Amy; Yeo, Michele; Telfer, Michelle; Sawyer, Susan M. (Frontiers in Psychiatry, 2020)
Objective Incorporating consumer perspectives is an important but often overlooked opportunity to optimize treatment engagement and outcomes for adolescents with eating disorders. This study explored the experience of care of adolescents and their parents at a multidisciplinary specialist eating disorders service providing family-based treatment (FBT) as first-line treatment. Method Eighty-five adolescents and 145 parents who completed FBT at the service between 2013 and 2015 were surveyed in 2017 about their experience of care. A study-designed survey asked respondents to rate on Likert scales their experience of service access, intake assessment, education, support, interactions with the treatment team, recovery, and the discharge process. Open-ended comments on helpful and unhelpful aspects of the service provided further context on the ratings. Results Overall families were very positive about their experience, particularly in regard to assessment, education, interactions with the team, and achieving physical health. Although parents tended to be more satisfied, adolescents also held the service in high regard. Some areas were identified that could be improved, including treatment delays, carer support, therapeutic alliance, and preparation for discharge. Conclusions Surveying families about their experience of care provides an important opportunity to identify service strengths as well as services gaps. The results indicated several areas that specialist eating disorder services could focus on to ensure that the services provided, including FBT, fully meet the needs of families and optimize adolescents’ treatment experiences.